2015
DOI: 10.1007/s11071-015-2160-8
|View full text |Cite
|
Sign up to set email alerts
|

Revealing network topology and dynamical parameters in delay-coupled complex network subjected to random noise

Abstract: It is well known that random noise and time delay are two inherent ingredients in complex networks, whose dynamical parameters and topological structures are often unknown or uncertain. This paper will employ the techniques of impulsive control and adaptive control to infer dynamical parameters and network topology in delay-coupled complex network under circumstance noise. By constructing an appropriate adaptive-impulsive control strategy in the response network, the unknown dynamical parameters and topology s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Li et al [13] and Timme [14] identified the phase oscillator network topology by repeating experiments many times based on phase synchronization, which needs a large amount of calculation for large-scale networks. Yang and Wei [15] and Liu et al [16] introduced the impulse control strategy for network topology identification to save the control energy. Stanković et al [17] proposed to estimate all system parameters utilizing a stochastic approximation algorithm with the expanding truncation derived from the modified Yule-Walker equations.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [13] and Timme [14] identified the phase oscillator network topology by repeating experiments many times based on phase synchronization, which needs a large amount of calculation for large-scale networks. Yang and Wei [15] and Liu et al [16] introduced the impulse control strategy for network topology identification to save the control energy. Stanković et al [17] proposed to estimate all system parameters utilizing a stochastic approximation algorithm with the expanding truncation derived from the modified Yule-Walker equations.…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of this approach is the necessity of disturbing oscillators in the network. Some methods exploit an auxiliary response network with the same intrinsic dynamics of the individual nodes as the drive network under study [6][7][8]. These methods use adaptive feedback control for synchronizing the drive and response networks, thus estimating the network connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is regarded as a fundamental tool in understanding a variety of dynamic phenomena which are presented in real worlds [1,2]. During the past years, a lot of related problems have been investigated for complex networks, for example, stability and synchronization [3][4][5][6][7], the analysis of complex networks with topological structures [8][9][10][11], pinning control [12][13][14], adaptive control [15][16][17], impulsive control [18,19], and robust analysis [20][21][22].…”
Section: Introductionmentioning
confidence: 99%